(untitled) (Fiep Bulletin - online, 2014)
This work objectives demonstrate the difference between the masses segmentares found in studies of Braune- Fischer (BF) and Zatsiorsky and Seluyanov (ZS). Because the studies of BF remontarem the first decades of the twentieth century and studies of ZS have around fifteen years and still are being subject to constant scientific research, our proposal in a sample of 7 persons (4 females and 3 of boys) is to establish the differences by percentage correlation between variables (correlation of Pearson) and check the cientificidade between the two methods of determining the masses segmentares for both sexes.